STUDY ON THE EVALUATION OF BREAST CANCER AND CERVICAL CANCER EARLY DETECTION PROGRAM IN SOUTH LAMPUNG 2016 - Sudarmi, Sudarmi; Nurchairini, Nurchairini (Journal of Education Research in Administration and Management (JERAM), 2017)
Abstract The objective of the study was to evaluate the implementation of the prevention/early detection program of breast and cervical cancer.  The type of research is Program Evaluation implementing CIPP model, the research methodology is qualitative, aimed to describe and analyze the phenomena, events, social activities, beliefs, perceptions, and peopleâ€™ thoughts either individually or in groups.  The research started from May until December 2016.  Data collection techniques employs documentation studies, interviews, observation, and active participation. The technique uses protocol research.    Data analysis is done by conducting tests or data validity assessment, classification of data based on sub focus and research questions, combination of data in matrix or table form, making data-based conclusions and triangulation strategies.  The evaluation results of the implementation of breast and cervical cancer early detection program, being carried out starting from the objectives until the enactment and monitoring is said to be good enough, but not yet up to the standard of evaluation criteria that have been set. Recommendations are addressed to the Health Department and its staffs in order to increase stakeholder involvement in planning, and in cancer detection process is expected to be in accordance with the Standard Operating Procedures (SOP) so that the expected program objectives can be achieved.   Key Words:   Early detection of cancer, cervical cancer, breast cancer, evaluation of program.